Explore the Motivational Factors Driving Economic Engagement among the Elderly in Rural Area in Lao People's Democratic Republic - Xaypaseuth, Soundala (Magyar Gerontológia, 2023)
This exploratory study delves into the motivational factors driving economic engagement among the elderly in rural areas of Laos, a nation in Southeast Asia experiencing demographic shifts towards an aging population. With limited research on this topic in the context of rural Laos, this study aims to uncover the underlying motivations that influence elderly individuals to participate in economic activities. By understanding these factors, policymakers can design targeted interventions to promote economic inclusion and improve the well-being of the elderly population. However, the study also uncovers barriers and challenges faced by elderly individuals, such as limited access to resources, skills, and infrastructure. Recommendations are provided to address these challenges and enhance support systems.